Correlation between iron-containing biochar with biogas yield from anaerobic digestion of food waste - Zulekhan, . (2024)
Food waste is one of the highest wastages generated annually, comprised of carbohydrates, proteins, lipids, and fiber contents which are suitable for degradation to methane via the anaerobic digestion (AD) process. However, biogas production has a low yield due to the inhibition of microbial activities, which consequently results in the instability of the AD system. The fundamental works involving the analysis of biochar properties, investigation of AD reaction parameters, and proposed reaction mechanism were the objectives of this study. The properties of biochar at different preparation temperatures were characterized and analyzed during the AD parameters studies, which include pH, retention time, organic loading rate (OLR), sludge dosage, and biochar dosage towards the biogas yield. Lastly, the role of the biochar properties towards the AD activity was investigated to elucidate the mechanism of sequestering product inhibition in the digestion stability of food waste for methane derivation. During the experiment, AD of food waste was conducted, and iron-containing sludge and iron-containing biochar were added at different dosage as an additive material. Results have indicated that biogas production was extremely low and poor without additives in the AD of food waste. The experimental findings revealed that the biogas yield increased by 11.95% with the additive of iron-containing sludge to the AD of food waste under the optimal conditions with 50g of feedstock, 4g of sludge and pH 7, process duration of 14 days and the biogas yield increased by 26.76% with the additive of iron-containing biochar to the AD of food waste under the optimal conditions with 50g of feedstock, 3g of iron-containing biochar and pH 4, process duration of 14 days as compared to without additive. Furthermore, the characterization analysis of iron-containing sludge and iron-containing biochar identified the -OH, C-H, C-C and C-O functions by Fourier-transform infrared (FTIR) spectroscopy, Brunauer-Emmett-Teller (BET) surface area decreased from 22.4m2 /g to 13.3m2 /g and high iron content through ICP-MS analysis. Iron serves as a micronutrient for certain microorganisms involved in AD. These microorganisms play key roles in decomposing organic matter and producing biogas. Iron-containing biochar can enhance these microbial populations' growth and activity by alleviating ammonia accumulation and increasing the activity of hydrogenotrophic methanogens. This study provides scientific support for applying biochar to solve the system inhibition in the AD of food waste.